Physical Activity, Maternal Metabolic Measures, and the Incidence of Gallbladder Sludge or Stones during Pregnancy: A Randomized Trial - Ko, Cynthia W.; Napolitano, Peter G.; Lee, Sum P.; Schulte, Scott D.; Ciol, Marcia A.; Beresford, Shirley A. A. (American Journal of Perinatology, 2014)
Objective To evaluate the effect of a physical activity intervention upon the incidence of gallbladder sludge or stones during pregnancy.Study Design Pregnant women without gallstones were randomized to an intervention to increase moderate to vigorous physical activity or control. Intervention group women received motivational materials and small-group instruction to increase physical activity. Gallbladder ultrasound and blood draws were obtained at entry, 18 weeks' gestation, and 36 weeks' gestation. Results In all, 591 were randomized to the intervention and 605 women to control groups. Women in the intervention group reported modestly higher levels of physical activity compared with control women, and fewer women in the intervention group reported no physical activity during pregnancy. The incidence of gallbladder sludge or stones was similar in intervention and control groups at 18 weeks (4.8% versus 5.4%; relative risk 0.89; 95% confidence interval 0.53, 1.47) and 36 weeks (4.3% versus 3.3%; relative risk 1.31; 95% confidence interval 0.70, 2.54). Fasting glucose, lipid, insulin, leptin, and adiponectin levels were similar in the two groups, as was insulin sensitivity and the incidence of gestational diabetes.Conclusion An intervention to increase moderate to vigorous physical activity did not decrease the incidence of gallbladder sludge or stones during pregnancy and did not result in improvement in maternal metabolic measures.
Keywords: cholelithiasis; physical activity; pregnancy/complications; insulin resistance; insulin